The Role of Social Capital, Social Media Marketing, and Entrepreneurial Orientation in the Success of Small and Medium Enterprises in the Tourism Industry - Dicky Hida Syahchari; Maria Grace Herlina; Azizah Omar (Binus Business Review, 2023)
The rapid growth of tourism sector can positively impact the performance of Small and Medium Enterprises (SMEs) in the tourism industry. However, the performance of tourism SMEs largely depends on how many domestic and international tourists arrive in Indonesia. The research aimed to determine the effect of social capital, social media marketing, and entrepreneurial orientation on the performance of tourism SMEs in Greater Jakarta. These indicators were adapted from several previous researchers. The research applied a quantitative approach. The primary data were obtained through interviews and questionnaires from 116 tourism SMEs. Then, the research analyzed the data using a Likert scale and Partial Least Squares-Structural Equations Model (PLS-SEM). The results support the acceptance of all three hypotheses, indicating that social capital, social media marketing, and entrepreneurial orientation significantly impact the performance of SME tourism. The research suggests substantial implications for tourism businesses and policies in Greater Jakarta. Strengthening social capital is essential for SMEs by requiring networking with business partners, suppliers, and local communities. Similarly, promoting marketing through social networks and investing in content strategies, targeted advertising, and collaboration with influencers are necessary. SMEs must apply an entrepreneurial perspective by encouraging innovation, new opportunities, and adaptation. Last, the government and stakeholders must support programs and policies that stimulate the development of these elements that contribute to the growth and sustainability of the tourism sector in the region.